Pengaruh Pemberian Berbagai Macam Gula Alami Terhadap Profil Darah Dan Performans Ayam Jawa Super Fase Starter - Kostomy Yusuf Prajalika; Suhardi; Wulandari (Wahana Peternakan, 2018)
Super Java chicken is a local Indonesian chicken whose life is closely related to the community. The purpose of this study was to determine the effect of bioavailability of natural sugar in drinking water on blood sugar levels, and performance on super stratum Javanese chickens.This study was conducted using 100 chickens divided into 4 treatments and examined for 4 days. The treatment applied is T0: administration of T1 mineral water: giving brown sugar drinking water (10%) T2: giving sugar cane water (4.5%) T3: giving pure honey drinking water (7.2%). The parameters observed were ration, blood sugar, body weight, intestinal length and liver weight. Data were tested by Duncan test, to find out the differences between treatments.The real effect on feed consumption shows that the treatment of T1 with the provision of brown sugar drinking water produces the highest feed consumption of 43.10 g / head. The high feed consumption in T1 correlates with high body weight growth. The chicken body weight in the study was the highest, namely in the treatment of 7.2% pure honey drinking water with body weight 13.88 g / head. Blood sampling is done 3 times, namely at 05.00, 07.00, 09.00. The highest average blood sugar level is T1 (298,47). The results showed that the administration of natural sugar water in the super chicken Java starter phase did not significantly affect intestinal length and liver weight.The conclusion of this study is that the provision of brown sugar is more effective than the administration of other natural sugars. Keywords: Java super starter phase, natural sugar, blood glucose, chicken performance